Responsible innovation in start-ups: entrepreneurial perspectives and formalisation of social responsibility - Simeon Veloudis; Mark Ryan; Elina Ketikidi; Vincent Blok (Journal of Responsible Innovation)
Start-ups are significant incubators of innovation. Notwithstanding, they have largely been ignored in the field of Responsible Innovation (RI). To address this shortcoming, the social responsibility for start-ups model (SRSM) for the embedment of RI in the innovation process of early-stage STEM (Science Technology Engineering Mathematics) start-ups has recently been proposed. Nevertheless, the SRSM is a model that still exists at the conceptual level. Therefore, it must be tested to confirm its legitimacy. In this paper, we propose a dedicated research methodology based on Social Labs for testing the SRSM through social experimentation; we also put this methodology into practice through an empirical case study aiming at operationalising RI in start-ups. A major finding of our study is that the SRSM constitutes an appropriate approach for institutionalising RI in start-ups, and for measuring the degree to which a startup innovates responsibly.